Study on hydrocephalus and complications of surgical treatment - Kadhim, Saad F.; Al- Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Shunt operations are performed for different reasons mainly hydrocephalus congenital or acquired. It’s associated with certain morbidity and mortality. Patients and method: A prospective study from Jan 2004 to Jan 2006, 226 patients under went shunt operation in the specialized surgical hospital in Baghdad. The patients were divided into two groups according to the way of applying the upper end catheter. In group A49 patients where posterior parietal approach was used, and group (B) 174 where parietal or temproprietal approach was used. Results and discussions: different complications were recorded, but the most frequent was upper end obstruction by choroids plexus or by debris. In group (A) only one patient 2% while in group (B) 27 patients 15.5% this wide difference in incidence of this complication, clears the significance of posterior parietal approach as a method of choice in applying ventricular catheter. Other complications were recorded as infection, lower end obstruction of others. A low rate of mortality recorded and discussed thoroughly. Conclusion: Choosing the post parietal type with prophylactic antibiotics carries the best results.